Students’ Voices of the Use of Facebook and Instagram in Teaching English in the University Context - Murni Mahmud; Salasiah Ammade; Abdul Halim; Fatimah Hidayahni Amin (Universitas Negeri Makassar, 2022)
Today the world of social media has immersed in the world of education and influencing the world of the students’ activities. It is inevitable that students in many levels of education have been using social media in their life either as students or as interactants in the certain community. Therefore, it is interesting to see the existence of social media among the students. In this study, the researchers highlight the use of social media among the students in the university. This research applied a qualitative research design taking 60 students of English in the universities in Makassar. The data of this research were collected by employing a survey of Google Form and analyzed descriptively and qualitatively. The result of the research shows that the English students in the universities in Makassar gave their positive perceptions about the use of social media. The informants has been using social media in their daily life and also nowadays has applied the social media as a tool of learning English. Some advantages and strategies in using social media in learning English were displayed in this study. Findings from this study will become important input for students themselves in the university context and also as beneficial information among the university practitioners in order to make use the social media in the university not only as communication tool but also as learning and teaching tools.